Psychodermatology — a current challenge for the therapeutic team - Baranowska, Anna; Krajewska-Kułak, Elżbieta; Jankowiak, Barbara; Klimaszewska, Krystyna; Kondzior, Dorota; Krajewska-Ferishah, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Psychodermatology is a branch of medicine that describes the interaction between dermatology and psychiatry, a new part of medicine, which combines dermatology, psychology and psychiatry. Skin lesions are visible and they may influence the patient’s psyche. Psychological factors are important in the pathology of several dermatoses. The incidence of psychiatric disorders among the dermatological patients is estimated at 30 to 60%. Psychodermatological diseases are divided into three groups, aiming at arriving at proper diagnosis. The knowledge and awareness of psychodermatology may improve physician’s diagnosis and differentiation enabling introduction of the therapeutic intervention in the field of psychopharmacology. Problemy Pielęgniarstwa 2012; 20 (4): 512–518